Energy Market Investment Methodologies - Matyas Tímea Bernadett (European Scientific Journal, ESJ, 2022)
As more and more renewable energy market investment opportunities come to the fore, investors intend to optimize their assets through risk-return diversification. In the light of Markowitz’s modern portfolio theory aimed at recognizing the potential for higher returns and lower risks, the identification of different energy market segments has become essential. In this regard, through the research of the conventional and alternative/ renewable energy market segments, as well as various international statistical models, the optimal methodology was identified. The optimal methodology allows the aggregation of different energy and alternative/ renewable energy ETFs into international investment portfolios using a variable weighing of assets and is expected to result in an adequate outcome.